The Relationship between Cooperation Atmosphere and Innovative Work Behavior of College In-Service Teachers in China: The Mediating Effect of Knowledge Sharing - Liu, Qian; Chang, Yuan Cheng (The international journal of diversity in education, 2024)
The only way to achieve sustainable competitiveness among universities in a competitive market is to cultivate and motivate innovative behavior among teachers. Building on knowledge management theory, this study empirically explores the relationship between an atmosphere of cooperation among university teachers and their innovative work behavior. The mediating effect of knowledge sharing is also examined, aiming to provide a significant theoretical basis for better promoting innovative work behavior in universities. As an exploratory correlational research, the study uses a questionnaire survey method, with 437 in-service teachers from four universities in Hebei Province as the research subjects. The results of the study are as follows: an atmosphere of cooperation among teachers in Hebei Province has a significantly positive impact on innovative work behavior; a cooperative atmosphere among teachers in Hebei Province has a significantly positive impact on knowledge sharing; knowledge sharing among teachers in Hebei Province has a significantly positive impact on innovative work behavior; there is a significant mediating effect of knowledge sharing between a cooperative atmosphere among teachers and innovative work behavior in Hebei Province.